Interobserver Agreement Rates on Fibroblast Activation Protein Inhibitor–Directed Molecular Imaging and Therapy. (19th June 2022) - Serfling, Sebastian E.; Hartrampf, Philipp E.; Zhi, Yingjun; Higuchi, Takahiro; Rowe, Steven P.; Bundschuh, Lena; Essler, Markus; Buck, Andreas K.; Bundschuh, Ralph Alexander; Werner, Rudolf A.
Abstract : Objectives: Fibroblast activation protein (FAP) has emerged as a novel target for FAP inhibitor (FAPI)–directed molecular imaging and endoradiotherapy (ERT). We aimed to assess the interobserver agreement rates for interpretation of 68 Ga-FAPI-4 PET/CT and decision for ERT. Patients and Methods: A random order of 68 Ga-FAPI-4 PET/CTs from 49 oncology patients were independently interpreted by 4 blinded readers. Per scan, visual assessment was performed, including overall scan impression, number of organ/lymph node (LN) metastases, and number of affected organs/LN regions. Moreover, a maximum of 3 target lesions, defined as largest in size and/or most intense, per organ compartment were identified, which allowed for an additional quantitative interobserver assessment of LN and organ lesions. To investigate potential reference tissues, quantification also included unaffected liver parenchyma and blood pool. Readers also had to indicate whether FAPI-directed ERT should be considered (based on intensity of uptake and widespread disease). Interobserver agreement rates were evaluated using intraclass correlation coefficients (ICCs) and interpreted according to Cicchetti (with 0.4–0.59 indicating fair, and 0.6–0.74 good, agreement). Results: On a visual basis, the agreement rate for an overall scan impression was fair (ICC, 0.42; 95% confidence interval [CI], 0.27–0.57). The concordance rate for number of affected LN areas was also fair (ICC, 0.59; 95% CI, 0.45–0.72), whereas the number of LN metastases, number of affected organs, and number of organ metastases achieved good agreement rates (ICC, ≥0.63). In a quantitative analysis, concordance rates for LN were good (ICC, 0.70; 0.48–0.88), but only fair for organ lesions (ICC, 0.43; 0.26–0.60). In regards to background tissues, ICCs were good for unaffected liver parenchyma (0.68; 0.54–0.79) and fair for blood pool (0.43; 0.29–0.58). When readers should decide on ERT, concordance rates were also fair (ICC, 0.59; 95% CI, 0.46–0.73). Conclusions: For FAPI-directed molecular imaging and therapy, a fair to good interobserver agreement rate was achieved, supporting the adoption of this radiotracer for clinical routine and multicenter trials.